ANALISIS KINERJA PEGAWAI BALAI KONSERVASI BOROBUDUR - Wahyanto, Dwi; Wikaningtyas, Suci Utami (Jurnal Riset Mahasiswa, 2024)
The success of an organization cannot be separated from the quality of an employee's performance. Government Regulation No. 30 of 2019 concerning Civil Servant Performance Assessment states that government employees are required to achieve Employee Performance Targets (SKP). Government employees performance assessment aims to ensure the objectivity of government employees coaching which is based on an achievement system and a career system. The purpose of this study was to analyze the performance of the staff of the Borobudur Conservation Office. This study used a qualitative descriptive approach, comparative qualitative and qualitative formulative. The research was conducted at the Borobudur Conservation Office in March 2021. Data was collected through in-depth interviews and documentation studies. Data analysis method used in this research was inductive using phenomenological procedures. The performance of Borobudur Conservation Office employees is still not good due to a lack of human resources, poor management of human resources, leadership factors, lack of coordination, lack of trust among employees, delays in carrying out tasks, and lack of integrity or awareness of duties.